Sri Lanka : Ending Poverty and Promoting Shared Prosperity - World Bank Group (World Bank, Washington, DC, 2015)
Between 2002 and 2012-13, most of the reduction in poverty was due to increased earnings, as opposed to higher employment or higher transfers. Although it is hard to be certain, increases in earnings are associated with: (i) a slow structural transformation away from agriculture and into industry and services that led to productivity increases; (ii) agglomeration around key urban areas that supported this structural transformation; (iii) domestic-driven growth, including public-sector investment that led to increases in labor demand, particularly in industry and services; and (iv) a commodity boom that led to higher labor earnings for agricultural workers in the context of lower agricultural employment. Sri Lanka’s has had impressive development gains but there are strong indications that drivers of past progress are not sustainable. Solid economic growth, strong poverty reduction, overcoming internal conflict, effecting a remarkable democratic transition in recent months, and overall strong human development outcomes are a track record that would make any country proud. However, the country’s inward looking growth model based on non-tradable sectors and domestic demand amplified by public investment cannot be expected to lead to sustained inclusive growth going forward. A systematic diagnostic points to fiscal, competitiveness, and inclusion challenges as well as cross-cutting governance and sustainability challenges as priority areas of focus for sustaining progress in ending poverty and promoting shared prosperity.